Korelasi antara Literasi Bahasa Indonesia dan Literasi Numerasi Matematika Siswa dalam Menyelesaikan Soal Matematika - Aziz, Saddam Al; Septriyanti, Yesi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This research includes ex post facto correlation research, which aims to determine the correlation of the independent (free) variable, namely Indonesian Language Literacy (X), with the dependent variable (tied), namely Mathematical Numerical Literacy (Y). The research was conducted in the January-June 2023 semester in 1 class VIII containing 30 students at a junior high school in Padang. Data was collected by testing one-story test questions. The sampling technique is purposive sampling. Data were analyzed using the Spearman Rank Correlation using the Kolmogorov-Smirnov normality test and hypothesis testing. The correlation coefficient value of Indonesian language literacy with the mathematical numeracy literacy variable is